The relationship between coronary artery disease and clinical outcomes in COVID-19: a single-center retrospective analysis. Issue 5 (23rd July 2020) - Peterson, Eric; Lo, Kevin Bryan; DeJoy, Robert; Salacup, Grace; Pelayo, Jerald; Bhargav, Ruchika; Gul, Fahad; Albano, Jeri; Azmaiparashvili, Zurab; Amanullah, Aman; Patarroyo-Aponte, Gabriel
Abstract : Introduction: Recent studies have reported evidence that coronavirus disease 2019 (COVID-19) has disproportionately affected patients with underlying comorbidities. Our study aims to evaluate the impact of both cardiac and noncardiac comorbidities on a high-risk population with COVID-19 infection and coronary artery disease (CAD) compared to those without CAD. Methods: This is a retrospective study of patients who tested COVID-19 positive via reverse transcriptase-PCR (RT-PCR) assay. We compared the characteristics and outcomes of patients with and without CAD. Population demographics, comorbidities and clinical outcomes were collected and analyzed. Multivariate logistic regression analysis was used to identify factors associated with inpatient mortality. Results: A final sample population of 355 patients was identified, 77 of which had a known diagnosis of coronary artery disease. Our study population had a higher proportion of females, and those with CAD were significantly older. The rates of cardiovascular risk factors including hypertension, diabetes mellitus and chronic kidney disease, as well as heart failure and chronic obstructive pulmonary disease were significantly higher in the CAD population. Lactate dehydrogenase was the only inflammatory marker significantly lower in the CAD group, while troponin and brain natriuretic peptide were significantly higher in this population. Patients with CAD also had significantly higher inpatient mortality (31% vs 20%, P = 0.046) and need for renal replacement therapy (33% vs 11%, P < 0.0001) compared to the non-CAD group. However, only age [odds ratio 1.041 (1.017–1.066), P = 0.001] was significantly associated with mortality in the overall population after adjusting for demographics and comorbidities, while the presence of CAD was not independently associated with mortality. Conclusion: Patients with CAD and COVID-19 have higher rates of comorbidities, inpatient mortality and need for renal replacement therapy compared to their non-CAD counterparts. However, CAD in itself was not associated with mortality after adjusting for other covariates, suggesting that other factors may play a larger role in the increased mortality and poor outcomes in these patients.